Correlation Between Folklore Implemented in Teaching and Student’s Character Toward English Learning Outcomes - Nihta V. F. Liando; Tiffany E. Pelleng; Ceisy N. Wuntu (International Journal of Education, Information Technology, and Others, 2021)
The study aims to find out the correlation between folklore implemented in teaching and student’s character toward English learning outcomes in the first grade of one vocational high school in Minahasa. It involved one class of first grade grade with 30 students each in academic year 2020/2021. The data analysis technique includes the presentation / description of the data, testing the analysis requirements and testing the hypothesis as follows. The data analysis technique includes the presentation and description of the data, testing the analysis requirements and testing the hypothesis as follows. The data analysis technique includes the presentation / description of the data, testing the analysis requirements and testing the hypothesis as follows. The results of this study indicate that there is a positive relationship between (a) Folklore implemented in teaching with the English learning outcome (0.321), (b) there is a positive relationship between students’ character with the English learning outcome (0.003), (c) there is a significant relationship between Folklore implemented in teaching and students’ character with the English learning outcome (0.538). Thus, it could be concluded that folklore implemented in teaching activities